The Effect of Elaborative Interrogation on the Synthesis of Ideas from Multiple Sources of Information - Farooq Omer (Open Information Science, 2019)
The new Framework for Information Literacy for Higher Education (ACRL, 2016) highlights the ability to synthesize ideas from multiple sources of information as one of the key knowledge practices. There is little generalizable empirical research based on cognitive science principles to guide information literacy instruction practice. The present study examined the effectiveness of elaborative interrogation instructional strategy on integration and transformation of ideas from multiple sources of information. 86 participants took part in the study via Amazon Mechanical Turk platform. The experiment involved reading five texts on the topic of climate change and responding to embedded elaborative interrogation prompts (treatment groups only), and writing a synthesis paragraph on the topic. Two one-way ANCOVAs were employed to test the hypotheses which indicated that elaborative interrogation prompts did not significantly improve performance on transformation and integration measures. This study contributes to the growing body of literature addressing information literacy instruction based on the new Framework and provides a promising long-term cross-disciplinary research partnership in terms of linking evidencebased guidance for instruction based on cognitive science principles to information literacy knowledge practices in the new Framework.